Effect of Additives on Impact Strength of Denture Base Resin - Hussain, Wafaa A.; Hashim, Furqan Salim (Iraqi Journal of Science, 2022)
This research has studied the effect of addition glass fibers (woven and chopped)and Zirconium oxide Nano-particles (ZrO2) with different weight percent to theconventional poly (methyl methacrylate) (PMMA). The prepared Nano-crystallineZrO2 powder with particle size of about 95nm was syntheses directly by sol-gelmethod. The gel dried at 100oC for 1 hour and annelid at 400oC for 3 hours.The conventional acrylic resin prepared with 2:1 powder to liquid ratio to preparepure sample, composite samples prepared by reinforcing PMMA with woven orchopped glass fiber (8, 12) wt.%, and reinforcing by (1,2,3) wt.% of prepared ZrO2Nano-powder.The structural tests include: (XRD, AFM, and FTIR). The crystallized phasecomposition of dried ZrO2 powder after annealing in air at 400oC has been identifiedby x-ray diffractometry (XRD). The grain size of dried ZrO2 Nano-particles byatomic force microscope (AFM).The impact strength (I.S.) was measured by using Charpy impact test. Themechanical test done in order to compare the impact strength between pure andcomposite samples. From the result, the reinforcing PMMA with glass fiber in twoforms (woven and chopped) improve the impact strength, while increasing of ZrO2Nano powder loading led to decrease the impact strength.